Optimization of the activity of CaO/Al2O3 catalyst for biodiesel production using response surface methodology - Zabeti, M.; Daud, Wan Mohd Ashri Wan; Aroua, Mohamed Kheireddine (Elsevier, 2009)
In this work the response surface methodology (RSM) in conjunction with the central composite design (CCD) were used to optimize the activity of CaO/Al2O3 solid catalysts for the production of biodiesel. In order to measure the catalyst activity, we used palm oil as a representative raw material for the conversion to biodiesel. The biodiesel production was carried out in a batch laboratory scale reactor. The results showed that both the calcination temperature and the amount of calcium oxide loaded on the support had significant positive effects on the biodiesel yield. The maximum basicity and biodiesel yield obtained were about 194 Î¼mol/g and 94, respectively. Overall, the catalyst showed high performance at moderate operating conditions and its activity was maintained after two cycles.